The treatment of anterior tooth crowded case of upper jaw with dental transposition between canine and lateral incisor tooth by fixed appliance - Dr.drg. Tita Ratya Utari, Sp.Ort (Journal PDGI, 2012)
this paper aims to report the successful treatment of a canine complete transposition case with upper lateral incisor done at a patient